Investment in construction and economic growth: a long-term perspective - Lopes, Jorge (2012)
The role of construction in economic growth and development has been addressed by various writers and international bodies, many of whom have focused in developing countries (Turin, 1973; World Bank, 1984; Wells, 1986; Bon, 1990). Bon (1992), analysed the changing role of the construction sector at various stages of economic development and presented a development pattern for the industry based on the stage of development of a country’s economy. The main aspects of the proposition were that, in the early stages of the economic development, the share of construction in gross domestic product (GDP) increases but ultimately decreases in industrially advanced countries. Turin and Wells, using cross-country comparisons, both found an association between construction investment and economic growth. That finding was consistent with the classical approach in growth theory in which physical capital formation is the main engine of economic growth and development. In the aftermath of the !979-980 oil-shock and the international financial crisis that followed in 1981, most of Sub- Saharan African countries experienced until the mid-1990s a decreasing growth in per capita national income, despite heavy investment in construction and other physical capital over the preceding decade.